Answer:
3/4 : 3/8 = 3/4 * 8/3 = 1/4 * 8/1 = 1/1 * 2/1 = 2
Answer:we smoking fredoooooooooo
Start with
![\dfrac{x}{2}+\dfrac{3}{2}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%7D%7B2%7D%2B%5Cdfrac%7B3%7D%7B2%7D%3C%5Cdfrac%7B5%7D%7B2%7D)
Multiply the whole equation by 2. Since 2 is positive, we don't need to switch the inequality sign:
![x+3](https://tex.z-dn.net/?f=x%2B3%3C5)
Subtract 3 from both sides:
![x](https://tex.z-dn.net/?f=x%3C2)
Answer:
![\boxed{f(x) - g(x) = 2x(2x^{2} + x + 1)}](https://tex.z-dn.net/?f=%5Cboxed%7Bf%28x%29%20-%20g%28x%29%20%3D%202x%282x%5E%7B2%7D%20%2B%20x%20%2B%201%29%7D)
Step-by-step explanation:
f(x) = 9x³ + 2x² - 5x + 4; g(x)=5x³ -7x + 4
Step 1. Calculate the difference between the functions
(a) Write the two functions, one above the other, in decreasing order of exponents.
ƒ(x) = 9x³ + 2x² - 5x + 4
g(x) = 5x³ - 7x + 4
(b) Create a subtraction problem using the two functions
ƒ(x) = 9x³ + 2x² - 5x + 4
-g(x) = <u>-(5x³ - 7x + 4)
</u>
ƒ(x) -g(x)=
(c). Subtract terms with the same exponent of x
ƒ(x) = 9x³ + 2x² - 5x + 4
-g(x) = <u>-(5x³ - 7x + 4)
</u>
ƒ(x) -g(x) = 4x³ + 2x² + 2x
Step 2. Factor the expression
y = 4x³ + 2x² + 2x
Factor 2x from each term
y = 2x(2x² + x + 1)
![\boxed{f(x) - g(x) = 2x(2x^{2} + x + 1)}](https://tex.z-dn.net/?f=%5Cboxed%7Bf%28x%29%20-%20g%28x%29%20%3D%202x%282x%5E%7B2%7D%20%2B%20x%20%2B%201%29%7D)
Answer:
3000 is your answer
Step-by-step explanation:
The 3 in the hundreds place if the number 587,349 has a value of 300. This 300 is 1/10 the value of the number you're looking for, so if x is the number you're looking for, then
![300 = \frac{1}{10} x](https://tex.z-dn.net/?f=300%20%3D%20%20%5Cfrac%7B1%7D%7B10%7D%20x)
![300 \times 10 = \frac{1}{10} x \times 10](https://tex.z-dn.net/?f=300%20%5Ctimes%2010%20%3D%20%20%5Cfrac%7B1%7D%7B10%7D%20x%20%5Ctimes%2010)
![3000 = x](https://tex.z-dn.net/?f=3000%20%3D%20x)
x is your answer.